Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

The Quest for Modern Manhood: Masculine Stereotypes, Peer Culture and the Social Significance of Homophobia - Plummer, David C. (Journal of Adolescence, 2001)
This paper explores the use of homophobic terms by boys and young men and the meanings they invoke when using them. Highly detailed interviews were conducted with young men from diverse backgrounds about their own experiences while growing up and their observations of schools, teachers, family and peers. Homophobia was found to be more than a simple prejudice against homosexuals. Homophobic terms like “poofter” and “faggot” have a rich developmental history and play a central role in adolescent male peer-group dynamics. Homophobic terms come into currency in primary school. When this happens, words like poofter and faggot rarely have sexual connotations. Nevertheless, far from being indiscriminate terms of abuse, these terms tap a complex array of meanings that are precisely mapped in peer cultures, and boys quickly learn to avoid homophobia and to use it decisively and with great impact against others. Significantly, this early, very powerful use of homophobic terms occurs prior to puberty, prior to adult sexual identity and prior to knowing much, if anything, about homosexuality. An effect of this sequence is that early homophobic experiences may well provide a key reference point for comprehending forthcoming adult sexual identity formation (gay or not) because powerful homophobic codes are learned first.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; australie; cours; discipline; homophobie; hétérosexisme; masculinité; nouvelle-zélande; océanie; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Les pratiques traditionnelles affectant la santé physique et mentale des femmes; l'excision et l'infibulation - situation actuelle et perspectives d'avenir - Vissandjée, B.; Ndejuru, R.; Kantiébo, M.; Renaud, J.; Aïthachimi, L.; Levine, L.; Lapointe, M. (Institut universitaire SHERPA, 2001)
L’excision et l’infibulation sont parties intégrantes des traditions de nombreuses sociétés africaines issues majoritairement de la région subsaharienne. En contexte canadien, aucune information statistique n’est présentement disponible sur la prédominance de cette pratique, malgré le fait que de nombreux intervenants soupçonnent que plusieurs immigrant(e)s en provenance de ces pays sont susceptibles de faire subir ces pratiques à leurs fillettes. Cette étude qualitative explore les valeurs et les croyances des immigrant(e)s par rapport à ces pratiques traditionnelles, tout en cernant les défis de leur processus d’intégration au Canada et leur recours aux services de santé.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; care; corps; cours; discipline; interculturalité; migration; médecine; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences; sciences humaines; sciences infirmières; sex2283; sexologie; sexualité; thématiques; violences